Risk aversion in agricultural water management investments in Northern Ghana: experimental evidence. (5th July 2018) - Katic, Pamela; Ellis, Tim
Abstract: Sub‐Saharan Africa (SSA) is one of the regions in the world most affected by food price volatility and production variability. Poor small‐scale farmers in this region are particularly vulnerable to this variability. As a result, households may be reluctant to adopt new agricultural water management (AWM) technologies when they involve more risk than what they mitigate. Despite risk's role in AWM investments, there have been few attempts to estimate the magnitude and nature of risk aversion in relation to this type of farm decisions. To partially close this gap, this article uses an experimental approach applied to 137 households in Northern Ghana. We find that more than 70% of households are moderately or slightly risk averse. This contrasts with other studies in SSA, where most household decision‐makers exhibit severe to extreme risk aversion. We also find that households that stand to lose as well as gain something from participation in games are less risk averse than households playing gains‐only games. This result suggests that most farmers' current wealth put them at risk of falling into a poverty trap. Thus, the losses from the riskiest investments on AWM technologies may fall more heavily on the poor, suggesting that additional efforts be given to the creation of viable insurance mechanisms.